Bottom-up behaviourally mediated trophic cascades in plankton food webs. Issue 1896 (6th February 2019) - van Someren Gréve, Hans; Kiørboe, Thomas; Almeda, Rodrigo
Abstract : Our traditional view of the interactions between marine organisms is conceptualized as food webs where species interact with one another mainly via direct consumption. However, recent research suggests that understudied non-consumptive interactions, such as behaviourally mediated indirect interactions (BMIIs), can influence marine ecosystems as much as consumptive effects. Here, we show, to our knowledge, the first experimental evidence and quantification of bottom-up BMIIs in plankton food webs. We used observational, modelling and experimental approaches to investigate how behavioural responses to resource availability influence predation mortality on grazers with different foraging strategies (ambushing versus active foraging). A three-level food chain was used: phytoplankton as resource, copepod nauplii as grazers of phytoplankton and a large copepod as a predator. Ambushers showed little change in foraging activity with resource availability, whereas active foragers decreased their foraging activity with increasing resources, which led to a decrease (24–50%) in predation mortality. Therefore, an increase in resources ('initiator') causes behavioural changes in active grazers ('transmitter'), which ultimately negatively affects predator ('receiver') consumption rates. Consequently, increase in resource abundance may result in decreasing energy transfer to higher trophic levels. These results indicate that behaviourally mediated interactions drive marine food web dynamics differently from that predicted by only density-mediated or consumptive interactions.